1969
DOI: 10.1139/o69-123
|View full text |Cite
|
Sign up to set email alerts
|

Disc electrophoresis of snake venoms. I. A qualitative comparison of the protein patterns from the species of Crotalidae and Elapidae

Abstract: The electrophoretic patterns of venom proteins of different species of snakes from the families of Crotalidae and Elapidae were studied by disc electrophoresis using different concentrations of polyacrylamide gel and different pH conditions. A qualitative comparison of the electropherograms showed variations in the distribution of proteins among different species and subspecies of snakes. It is suggested that the classification of venomous snakes from the standpoint of venom compositions is of fundamental impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In many previous studies (Tu & Ganthavorn 1968;Basu et al 1969;Bonilla & Horner 1969;Young & Miller, 1974), it has been reported that the secretions of Duvernoys gland in various colubrid snakes have important characteristic electrophoretic patterns and more similar complexities as compared to elapid and viperid venoms. Minton and Weinstein (1987) pointed out that the colubrid venoms they analysed using SDS-PAGE electrophoresis, contained 7-10 protein bands and that the Duvernoys gland secretion was as complex as most proteroglyph (Elapidae & Hydrophidae) venoms, but the total number of protein bands was lower than those of viperid snakes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In many previous studies (Tu & Ganthavorn 1968;Basu et al 1969;Bonilla & Horner 1969;Young & Miller, 1974), it has been reported that the secretions of Duvernoys gland in various colubrid snakes have important characteristic electrophoretic patterns and more similar complexities as compared to elapid and viperid venoms. Minton and Weinstein (1987) pointed out that the colubrid venoms they analysed using SDS-PAGE electrophoresis, contained 7-10 protein bands and that the Duvernoys gland secretion was as complex as most proteroglyph (Elapidae & Hydrophidae) venoms, but the total number of protein bands was lower than those of viperid snakes.…”
Section: Discussionmentioning
confidence: 98%
“…Although the Duvernoys gland is a homologue of the venom glands of viperid and elapid snakes, it is anatomically and functionally distinct (Kardong 2002). On different viperid, colubrid and elapid snake venoms; many electrophoretical studies were conducted (Tu & Ganthavorn 1968;Basu et al 1969;Bonilla & Horner 1969;Young & Miller 1974;Minton & Weinstein 1987). A notable biochemical study on Russells viper belongs to Tun-Pe et al (1995).…”
Section: Introductionmentioning
confidence: 99%